IMPLEMENTATION OF THE MERDEKA CURRICULUM IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS IN GRADE VII OF SMP IT INSAN HARAPAN KARAWANG ACADEMIC YEAR 2022 – 2023: IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS VII SMP IT INSAN HARAPAN KARAWANG TAHUN AJARAN 2022 – 2023 - Ayu; Rahmawati Rahmawati; Selawati Selawati; Tiara Sri Rahayu; Nur Aini Farida (Hawari: Jurnal Pendidikan Agama dan Keagamaan Islam, 2023)
The independent curriculum or what is known as independent learning is a form of government response to the condition of Indonesian education after the Covid-19 pandemic. This policy was launched as an effort by the government to help restore learning in Indonesia. This research was conducted at SMP IT Insan Harapan, Karawang. This study aims to explore the effectiveness of the independent curriculum in improving students' cognitive in PAI subjects using a cognitive learning theory approach. The method used in this study is descriptive qualitative to provide field notes regarding the implementation of the independent curriculum with data collection techniques through observation and interviews. The results of this study, SMP IT Insan Harapan has not fully implemented the new independent curriculum implemented in class VII. While grades VIII and IX are still using the 2013 curriculum, or it can be said that SMP IT Insan Harapan is still in the independent stage of change. But until now the implementation is very effective and can improve student learning outcomes. The implementation of the independent curriculum at SMP IT Insan Harapan is supported by students, teachers and school infrastructure. Keywords: Independent curriculum, learning outcomes, PAI